(untitled) (Homoeopathy for All, 2022)
Indigestion is not a disease. Indigestion is usually related to lifestyle and what we eat and drink. The main symptom is usually pain or discomfort in the upper tummy (abdomen). In addition, other symptoms that may develop include Bloating, Belching, Quickly feeling full after eating, Feeling sick (nausea) & Being sick (vomiting). Homoeopathy is a remarkable resource for those dealing with digestive disorders. Homoeopathy can be of assistance in retrieving normal motility and treating any psychological issues related to gastric disorders.